2003
DOI: 10.1002/j.1939-4640.2003.tb02714.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species and Cryopreservation Promote DNA Fragmentation in Equine Spermatozoa

Abstract: The objective of this study was to examine the effect of reactive oxygen species (ROS) and cryopreservation on DNA fragmentation of equine spermatozoa. In experiment 1, equine spermatozoa were incubated (1 hour, 38 degrees C) according to the following treatments: 1) sperm alone; 2) sperm + xanthine (X, 0.3 mM)-xanthine oxidase (XO, 0.025 U/mL); 3) sperm + X (0.6 mM)-XO (0.05 U/mL); and 4) sperm + X (1 mM)-XO (0.1 U/mL). In experiment 2, spermatozoa were incubated (1 hour, 38 degrees C) with X (1 mM)-XO (0.1 U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
1
17

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(148 citation statements)
references
References 86 publications
(117 reference statements)
7
121
1
17
Order By: Relevance
“…[73][74][75] In contrast to superoxide anion, the more stable H 2 O 2 readily crosses the plasma membrane and is responsible for DNA oxidative damage. 76 Because DNA integrity is essential for achieving fertilisation and enabling embryo development in assisted reproductive technologies, the preservation of DNA during cryostorage is of extreme importance. Several studies have examined antioxidative compounds that can protect sperm DNA from cryopreservation and thawing injuries.…”
Section: Gangliosides and Spermatozoamentioning
confidence: 99%
“…[73][74][75] In contrast to superoxide anion, the more stable H 2 O 2 readily crosses the plasma membrane and is responsible for DNA oxidative damage. 76 Because DNA integrity is essential for achieving fertilisation and enabling embryo development in assisted reproductive technologies, the preservation of DNA during cryostorage is of extreme importance. Several studies have examined antioxidative compounds that can protect sperm DNA from cryopreservation and thawing injuries.…”
Section: Gangliosides and Spermatozoamentioning
confidence: 99%
“…In addition to membrane effects, lipid peroxidation can also damage DNA. Baumber et al (2003) examined the effect of reactive oxygen species and cryopreservation on DNA of equine sperm. They demonstrated that reactive oxygen species and cryopreservation promotes DNA fragmentation in equine sperm.…”
Section: Advances In Freezing Semenmentioning
confidence: 99%
“…The most important is the production of Reactive Oxygen Species (ROS), which is excited by excessive stress, competitive sports, alcohol and drug abuse or nicotine. If produced in abundance, ROS can enter the cell nucleus, bind to the DNA and cause its fragmentation [32][33][34][35]. Several studies have reported that redox balance is deregulated in the ejaculates from infertile males, with glutathione peroxidase 4 as one of the main enzymes involved in this issue [36].…”
Section: Discussionmentioning
confidence: 99%